An Unlikely Cause of a Blunt Pancreatic Injury. Issue 12 (December 2019) - Cully, Matthew; Perry, Jonathan; Titus, M. Olivia
Abstract : Abstract: We report the case of a 17-year-old male football player with blunt abdominal trauma. Careful evaluation, including computed tomography and laboratory, revealed a pancreatic body laceration. Pancreatic injuries are relatively uncommon and associated with significant morbidity and mortality and require early diagnosis for optimal management and outcome.